Integrative Knowledge and Contemporary Issues: Evaluating Amin Abdullah's Paradigm of Multidisciplinarity - Dasrizal, Budiman; Suhail, Muhammad; Pradipta, Raihan (Islamic Thought Review, 2024)
This study investigates the evolving nature of knowledge in addressing contemporary issues that arise with rapid societal changes. Motivated by the need for adaptive solutions beyond traditional monodisciplinary approaches, this research examines the new paradigm introduced by Amin Abdullah in his seminal work, "MIT" (Multidisciplinary, Interdisciplinary, and Transdisciplinary). Employing a qualitative methodology with a library research approach, the study analyzes primary and secondary sources related to Abdullah's framework. Content and historical analysis techniques were utilized to interpret the data. The findings reveal that Abdullah’s paradigm integrates three clusters of knowledge—Naql (Revelation), Aql (Reason), and Qalb (Intuition)—through a trialogue involving subjective (religion), objective (science), and intersubjective (conscience) aspects. This approach promotes a comprehensive framework for addressing contemporary complexities by merging hadarah al-nas (religion), hadarah al-falsafah (philosophy), and hadarah al-‘ilm (science). Abdullah advocates for dialogical and integrative values, emphasizing semipermeable boundaries, intersubjective testability, and creative imagination as tools for effective problem-solving in a multifaceted world. This paradigm offers a significant shift from stagnant scientific approaches, proposing a dynamic model that fosters adaptability and holistic understanding.